2010
DOI: 10.1002/poc.1615
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐phase basicities of acetophenones toward lanthanum cation [La(OMe)]

Abstract: The relative free energy changes (lanthanum cation basicity, LaCB[L2]) for the reaction [La(OMe)2]L 2+ ⇌ La(OMe) 2+ + 2L were determined in the gas phase for m‐ and p‐substituted acetophenones based on the measurement of ligand exchange equilibria using an FT‐ICR mass spectrometer. The substituent effect on ΔLaCB[L2] of acetophenone is described in terms of the Yukawa–Tsuno equation, ΔG = ρ(σ° + r+ Δ σ R+), with a ρ value of −11.2 and an r+ value of 0.49. From this result, a ρ value of −7.0 and an r+ value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Careful examination of literature showed that deviations from Hammett plots based on standard σ‐values have been rarely reported in S E Ar reactions, but have been commonly observed in S N Ar and S N 2 process. Jamaoui and co‐workers, for example, investigated the reactions of 4‐chloro‐7‐nitrobenzofurazan with 4‐X‐substituted anilines (X = OH, OCH 3 , CH 3 , H, I Cl and CN) in dimethyl sulfoxide (Me 2 SO) solution at 25°C, and the curved Hammett plot has been interpreted in terms of a change in mechanism from a polar S N Ar process for less basic nucleophiles (X = I, Cl and CN) to a single‐electron transfer for more basic nucleophiles (X = OH, OCH 3 and CH 3 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Careful examination of literature showed that deviations from Hammett plots based on standard σ‐values have been rarely reported in S E Ar reactions, but have been commonly observed in S N Ar and S N 2 process. Jamaoui and co‐workers, for example, investigated the reactions of 4‐chloro‐7‐nitrobenzofurazan with 4‐X‐substituted anilines (X = OH, OCH 3 , CH 3 , H, I Cl and CN) in dimethyl sulfoxide (Me 2 SO) solution at 25°C, and the curved Hammett plot has been interpreted in terms of a change in mechanism from a polar S N Ar process for less basic nucleophiles (X = I, Cl and CN) to a single‐electron transfer for more basic nucleophiles (X = OH, OCH 3 and CH 3 ) .…”
Section: Resultsmentioning
confidence: 99%